Vegetative phase change in Populus tremula × alba. Issue 1 (1st April 2021) - Lawrence, Erica H.; Leichty, Aaron R.; Doody, Erin E.; Ma, Cathleen; Strauss, Steven H.; Poethig, R. Scott
Summary: Plants transition through juvenile and adult phases of vegetative development in a process known as vegetative phase change (VPC). In poplars (genus Populus ) the differences between these stages are subtle, making it difficult to determine when this transition occurs. Previous studies of VPC in poplars have relied on plants propagated in vitro, leaving the natural progression of this process unknown. We examined developmental morphology of seed‐grown and in vitro derived Populus tremula × alba (clone 717‐1B4), and compared the phenotype of these to transgenics with manipulated miR156 expression, the master regulator of VPC. In seed‐grown plants, most traits changed from node‐to‐node during the first 3 months of development but remained constant after node 25. Many traits remained unchanged in clones over‐expressing miR156, or were enhanced when miR156 was lowered, demonstrating their natural progression is regulated by the miR156/SPL pathway. The characteristic leaf fluttering of Populus is one of these miR156‐regulated traits. Vegetative development in plants grown from culture mirrored that of seed‐grown plants, allowing direct comparison between plants often used in research and those found in nature. These results provide a foundation for further research on the role of VPC in the ecology and evolution of this economically important genus.